2000
DOI: 10.1038/sj.onc.1203370
|View full text |Cite
|
Sign up to set email alerts
|

Dominant action of mutated erythropoietin receptors on differentiation in vitro and erythroleukemia development in vivo

Abstract: J2E cells produce rapid, fatal erythroleukemias in vivo but still respond to erythropoietin (epo) in vitro by di erentiating, proliferating and remaining viable in the absence of serum. Mutant epo receptors were introduced into these cells to determine whether they could in¯uence the di erent biological responses to epo in vitro and the development of erythroleukemias. Three mutant receptors were used as cytoplasmic truncation mutants D257 and D321 (above box 1 and below box 2 respectively), and the cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…5 Recently, the mechanism involved in erythropoiesis has become of great interest in understanding the role of growth factors and their receptors in leukemogenesis; altered hematopoietic growth factors and their receptors may contribute to tumorigenesis 6 and leukemogenesis. [7][8][9] The function of Epo may exist beyond hematopoietic tissues. Epo receptors exist in the paracrine and autocrine, as well as the hormonal systems.…”
mentioning
confidence: 99%
“…5 Recently, the mechanism involved in erythropoiesis has become of great interest in understanding the role of growth factors and their receptors in leukemogenesis; altered hematopoietic growth factors and their receptors may contribute to tumorigenesis 6 and leukemogenesis. [7][8][9] The function of Epo may exist beyond hematopoietic tissues. Epo receptors exist in the paracrine and autocrine, as well as the hormonal systems.…”
mentioning
confidence: 99%
“…IFN DNA therapy has clearly demonstrated that type I IFNs differ in their antiviral capacity and modulation of the immune response. 51,[57][58][59]93 Other investigators have found that type I IFN is a clinical target with promising antileukemic potential. In cancer treatment, IFN-␣ electroporation gene therapy results in tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previously, it has been shown that altering signaling molecules can impede the progression of erythroleukemia induced by J2E cells. 6,57 Therefore, since the IFN subtypes varied in their antigrowth, differentiation, cell viability, apoptotic response, and induced altered signaling pathways in J2E cells, we investigated their therapeutic potential for J2E cell-induced erythroleukemia. Mice were injected with IFN plasmid DNA into the TA muscle 2 weeks prior to intravenous injection of J2E cells, thus allowing expression of the transgene in vivo.…”
Section: Ifn Therapy For J2e Cell-induced Erythroleukemiamentioning
confidence: 99%
“…Manipulation of JAK2 and STAT5 activation was achieved by introduction of mutant Epo receptors into J2E cells. We have recently demonstrated that coexpression of wild-type Epo receptors with mutant receptors has marked biological consequences, that is, cells bearing the truncated D321 receptor are hypersensitive to Epo, whereas those containing the W282R point-mutant do not respond to Epo (Cull et al, 2000). The truncated D321 receptors lack the negative regulatory C-terminal domain (D'Andrea et al, 1991), whereas the W282R mutant fails to bind JAK2 (Miura et al, 1994)).…”
Section: Mutated Epo Receptors Affect Socs Gene Expressionmentioning
confidence: 99%
“…J2E cell lines infected with the pMSCV-neo 2.2 vector (Hawley et al, 1994) containing either a truncated Epo receptor (J-D321) or mutated JAK2 binding site receptor (J-W282R) are described elsewhere (Cull et al, 2000). Results from a representative clone of three original isolates are shown.…”
Section: Amphotropic Viral Infection Of Erythroid Cellsmentioning
confidence: 99%